Ramification of social-emotional learning on students’ academic success in English: A systematic literature review - Ni Made Rini Antari; Made Hery Santosa; Tin. T. Dang (English Learning Innovation, 2024)
This study aims to explore the previous research using systematic literature review related to the ramification between social-emotional learning competence (henceforth, SEL competence) and students’ academic achievement in English learning context related to the integration of SEL in English learning. The study also investigates whether SEL competence levels of EFL/ESL students and teachers are correlate with students’ academic success based on the literature review on the previous study related to the relationship between SEL and English achievement. This study belongs to systematic literature review using PRISMA model for data collection and thematic analysis to analyze the data. The result of systematic literature review showed that SEL competence has a positive correlation with EFL/ESL students’ academic achievement which means the higher SEL competence levels that students have, the higher score in English subject they have. The result also indicated both English teachers’ and students’ SEL competence levels are important for teaching and learning process which connected to the motivation that can increase students’ engagement to learn English. Result showed that the relationship between SEL competence levels and students’ academic achievement in EFL/ESL context linked to the integration of SEL in the classroom, SEL play an important role as the way for students to learn how to control themselves, their relationships, emotions, and SEL does not replace anything in classroom.